Body Temperature Monitoring System For Covid-19 Prevention Using Amg8833 Thermal Sensor Based On Internet Of Things - Muhammad Rusdi; Suprianto; Fitria Nova Hulu (Institute of Computer Science (IOCS), 2021)
The spread of the Covid-19 virus which continues to grow and is worrying to date with its increasing number of victims, encourages the Government to continue to take measures to prevent the spread of the Corona virus. One of the government's efforts to prevent COVID-19 is to monitor the health condition of the human body. One of them is detecting the human body temperature, because body temperature with a temperature above a certain limit is one of the symptoms of covid-19. The normal human body temperature ranges from 36 degrees to 37 degrees. However, for the current situation related to the corona virus pandemic, temperatures above 37 degrees have become temperatures that must be watched out for. This study aims to make a prototype of a body temperature monitoring system for the prevention of Covid-19 based on Internet of Things (IoT) The prototype designed uses an AMG8833 thermal sensor which will measure a person's body temperature with infrared which can identify a person's health through his body heat and also uses an ultrasonic sensor to measure a person's distance with the thermal sensor. The results of body temperature monitoring can be accessed on the cellphone through the blink application. From the results of the discussion, it was found that the body temperature monitoring system for the prevention of Covid-19 using AMG8833 thermal sensor the based on IoT was successfully designed and implemented in a prototype form. AMG 8833 thermal sensor works well in measuring human body temperature up to a distance of 20 with an average error of 1.18%. The level of accuracy of the body temperature monitoring system using the AMG 8833 thermal sensor is 98.82%.